The Implementation of Islamic Religious Education Learning in Forming Personal Akhlakul Karimah - Khotibul Umam, M.; Jannah, Siti Roudlhotul (International Journal on Advanced Science, Education, and Religion, 2024)
Research on the Implementation of Islamic Religious Education Learning in Forming Akhlakul Karimah. Many areas of human life are regulated by Islam. Likewise, Islam regulates the personal self of a Muslim to perfect morals, Rasulullah SAW said "indeed, I was sent by Allah SWT to perfect noble morals". As a Muslim in the current era, it is important to form a person with moral character so that he can protect himself from things that are prohibited by religion. In having good morals, a Muslim must respect himself and others more to apply good morals for himself, of course in accordance with the Al-Qur'an and Assunnah, both in deeds, words and morals towards Allah SWT, Rasulullah SAW and the final scholars. era. The aim of this research is as an effort to form moral character in the person of a Muslim. Rasulullah SAW said "There is nothing heavier in the scales of charity than good morals". The method used in this research is qualitative research using literature. Data sources come from journals, articles and books that study morals. The data obtained is collected in the form of notes then analyzed and conclusions drawn. Keywords: Muslim personality, Islamic religious education, Akhlakul Karimah